Multimode Speed Control Based on Fuzzy Decision-Making for Automatic Train Operation - Junnian Gou (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Based on the analysis of train running process and train motor-driven models, an ATO compound control algorithm of multimode fuzzy decision making is proposed, which will improve the effects of dynamic and static control of ATO system. Control weighting coefficients of PID controller output and fuzzy controller output are obtained by fuzzy reasoning, fuzzy decision-making and dynamic calculations of error and error rate of train speed, and also the weighting coefficients are used for the output calculation of fuzzy decision-making controller. Simulation results show the speed and accuracy of ATO speed control are improved effectively by the compound  multimode decision controller algorithm, which help to  improve the comfort of trains and its stop precision.